Activity and distribution of plasma platelet‐activating factor acetylhydrolase in women with gestational diabetes mellitus and their neonates. Issue 6 (7th March 2016) - Gao, Qian; He, Guo‐Lin; Zhang, Li; Bai, Huai; Liu, Xing‐Hui; Fan, Ping
Abstract: Background: Abnormal activity and distribution of plasma platelet‐activating factor acetylhydrolase (PAF‐AH) are associated with chronic inflammatory status. In this study, we investigate the activity and distribution of plasma PAF‐AH and their association with metabolic components in mothers with gestational diabetes mellitus (GDM) and in their neonates. Methods: Based on the International Association of Diabetes Pregnancy Study Group criteria, we performed a case‐controlled study of 101 women with GDM, 98 women with uncomplicated pregnancies, 142 neonates of mothers with GDM and 121 neonates of mothers with uncomplicated pregnancies. Plasma PAF‐AH, high‐density lipoprotein (HDL)‐associated PAF‐AH (H‐PAF‐AH) and apolipoprotein (apo) B‐containing lipoprotein‐associated PAF‐AH (apoB‐PAF‐AH) activities were measured using the trichloroacetic acid precipitation procedure with PAF C‐16 as a substrate. Results: The plasma PAF‐AH and apoB‐PAF‐AH activities, triglyceride (TG) levels, atherogenic index and TG/HDL‐C ratio were increased, and the H‐PAF‐AH proportions were decreased in the mothers with GDM compared with the control mothers ( p < 0.05). Multivariate regression analyses demonstrated that the apoB and TG levels were significant predictors of plasma PAF‐AH or apoB‐PAF‐AH activities, while the low‐density lipoprotein‐cholesterol levels, weight gain during pregnancy and age were associated with H‐PAF‐AH activities. The neonates of mothers with GDM had higher plasma insulin and glucose concentrations ( p < 0.05) and tended to exhibit increased serum apoB levels ( p = 0.062) compared with the neonates of mothers with uncomplicated pregnancies. Conclusions: The mothers with GDM presented with a state of chronic inflammation, and these mothers and their neonates also exhibited unfavourable metabolic profiles in terms of glucose and lipids. Copyright © 2016 John Wiley & Sons, Ltd.